Positive electrode material and secondary battery

By setting a metal oxide cladding layer on the surface of the positive electrode active material particles of the lithium-ion secondary battery, and controlling the ratio of its roundness and transition metal ion content, the battery performance attenuation caused by transition metal ion dissolution is solved, and excellent performance and safety are achieved in high temperature environments.

CN119764416AActive Publication Date: 2025-04-04CALB GROUP CO LTD

Patent Information

Application Number
CN202411990332.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The positive electrode active materials of existing lithium-ion secondary batteries have transition metal ion dissolution problems during the working process, resulting in attenuation of battery performance, which may cause safety problems in high temperature environments.

Method used

A metal oxide coating layer is provided on the surface of the positive electrode active material particles, and the stability and conductivity balance of the material are coordinated by regulating the ratio between the roundness of the coated positive electrode material and the proportion of the content of free transition metal ions after acid corrosion.

Benefits of technology

The secondary battery has excellent cycle stability and storage capacity retention rate in high temperature environments, avoiding performance attenuation and safety problems caused by the dissolution of transition metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223505900000201
    Figure BDA0005223505900000201
  • Figure BDA0005223505900000211
    Figure BDA0005223505900000211
  • Figure BDA0005223505900000221
    Figure BDA0005223505900000221
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a secondary battery, and belongs to the technical field of batteries, the material is characterized in that a coating layer is arranged on the surface of a positive electrode active substance, and meanwhile, the roundness of the coated positive electrode material and the ratio relation of the content ratio of free transition metal ions after the acid corrosion effect are regulated and controlled; the balance of the stability and the conductivity in the positive electrode material is coordinated, so that the secondary battery prepared from the positive electrode material has ideal electrochemical performance, and particularly has relatively excellent cycling stability and storage capacity retention rate in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material and a secondary battery. Background Art

[0002] In existing secondary batteries, especially lithium-ion secondary battery products, mainstream positive electrode active materials include ternary nickel cobalt manganese oxide materials, lithium iron phosphate and spinel nickel manganese oxide, etc. These materials have ideal electrochemical activity, but without exception have the problem of transition metal ion dissolution (for ternary materials, it is the dissolution problem of the three elements of nickel, cobalt and manganese, while lithium iron phosphate is the dissolution problem of iron, and lithium nickel manganese oxide is the dissolution problem of nickel and manganese). As a result, after the secondary battery has been working for a period of time, the probability of side reactions with the electrolyte after the transition metal ions are dissolved increases, the gas production increases, and the battery performance decays. Especially in high temperature environments, the degree of side reactions increases, and may even cause safety problems.

[0003] To this end, people have tried to coat and modify the positive electrode active materials, reducing the dissolution of transition metal ions through the inert protection of the coating layer. However, the coating layer materials used in this method are mostly insulating or semi-insulating materials with low conductivity, which affects the ion / electron transmission efficiency of the positive electrode active materials. Summary of the invention

[0004] The purpose of the present application is to overcome the shortcomings of the prior art and provide a positive electrode material, which has a coating layer on the surface of the positive electrode active material, and at the same time regulates the roundness of the coated positive electrode material and the ratio of the content of free transition metal ions after acid corrosion, so as to coordinate the balance between stability and conductivity in the positive electrode material, so that the secondary battery prepared by the positive electrode material has ideal electrochemical properties, especially has better cycle stability and storage capacity retention rate under high temperature environment.

[0005] To achieve the above object, in a first aspect of the present application, the present application provides a positive electrode material, including positive electrode active material particles, wherein the positive electrode active material particles are provided with a coating layer, wherein the coating layer includes a metal oxide;

[0006] The positive electrode material satisfies: 0.2≤K / Rn≤1.2;

[0007] The K% is the content ratio of the free transition metal element in the positive electrode active material particles after the positive electrode active material particles are immersed in a 20wt% hydrofluoric acid solution at a solid-liquid ratio of 1g:5mL at 70°C for 72h.

[0008] The Rn is the roundness of the positive electrode active material particles.

[0009] The beneficial effects of this application are:

[0010] The present application provides a positive electrode material, which has a coating layer on the surface of a positive electrode active material, and at the same time regulates the roundness of the coated positive electrode material and the ratio of the content of free transition metal ions after acid corrosion, so as to coordinate the balance between stability and conductivity in the positive electrode material, so that the secondary battery prepared by the positive electrode material has ideal electrochemical properties, especially has better cycle stability and storage capacity retention rate under high temperature environment. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0012] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0013] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0014] The present application is further described below with specific embodiments:

[0015] A positive electrode material comprises positive electrode active material particles, wherein the positive electrode active material particles are provided with a coating layer, wherein the coating layer comprises a metal oxide;

[0016] The positive electrode material satisfies: 0.2≤K / Rn≤1.2;

[0017] The K% is the content ratio of the free transition metal element in the positive electrode active material particles after the positive electrode active material particles are immersed in a 20 wt % hydrofluoric acid solution at a solid-liquid ratio of 1 g:5 mL at 70° C. for 72 hours.

[0018] The Rn is the roundness of the positive electrode active material particles.

[0019] Before the positive electrode active material is used in the positive electrode material, in order to suppress the dissolution of transition metal elements in the particles during the cyclic charge and discharge process, the probability of side reactions after contact with the electrolyte increases. Therefore, an inert metal oxide coating layer is generally provided on the surface of the particles. This phenomenon is suppressed through the isolation protection of the coating layer. However, the introduction of such a coating layer will hinder the ion / electron transport kinetics of the positive electrode active material particles, reduce the overall conductivity of the positive electrode active material particles, and ultimately exhibit low electrochemical performance. In order to overcome this technical difficulty, the technical solution of the present application sets a metal oxide coating layer on the surface of the positive electrode active material particles, and at the same time adjusts the coating effect of the coating layer by regulating the roundness of the coated positive electrode active material particles and the ratio of the content of free transition metal ions after acid corrosion, so as to coordinate the stability of the overall material after coating and the balance of the ion / electron transfer kinetics. The roundness of the positive electrode active material particles is related to the irregularity of the particle form and the surface flatness, thereby affecting the contact effect when it contacts the electrolyte and the overall path length of the ion / electron transfer. On the other hand, after the coating layer is set, the degree of freedom of the transition metal elements changes. By regulating the free content of the transition metal elements in the positive electrode active material particles after acid etching, the structural stability and ion / electron conduction properties of the material can be synchronously regulated. When the present application scheme controls the ratio K / Rn of the above two key factors within the range of 0.2 to 1.2, the positive electrode material can take into account both conductivity and structural stability when applied to secondary batteries, and the probability of side reactions after contact with the electrolyte is reduced, while the ion / electron transport kinetics of the material itself will not be weakened, and the secondary battery can exhibit excellent electrochemical performance. If the ratio K / Rn is improperly set, it may cause the probability of side reactions between the positive electrode active material particles and the electrolyte to be too high, affecting the service life of the secondary battery and even causing safety problems, or the charging and discharging efficiency of the secondary battery becomes low, and the energy density is reduced.

[0020] In some embodiments, the K / Rn is in the range of one or any two of 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2.

[0021] In some embodiments, the 0.4≤Rn≤0.8.

[0022] More preferably, the Rn is in the range of one or any two of 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8.

[0023] Further preferably, 0.6≤Rn≤0.7.

[0024] When the roundness of the positive electrode active material particles after setting the coating layer is low, it means that the surface flatness of the particles is low and the particle irregularity is high after coating, while when the roundness is high, it means that the coating integrity of the particles is good and the particle regularity is also high. The contact area of ​​positive electrode active material particles with different roundness when in contact with the electrolyte is also different. At the same time, the regularity of the particles will also make the compaction tightness and structural stability different when used to prepare pole pieces. When the roundness is preferably within the above range, the positive electrode active material particles can achieve a moderate contact area when in contact with the electrolyte, and the balance between the probability of transition metal ion dissolution and the difficulty of ion / electron transmission of the material can be regulated by the degree of coating. At the same time, ideal pole piece stability and density can be achieved when preparing the positive pole piece, so that the overall electrochemical performance of the material is better.

[0025] It should be noted that the test method for the roundness Rn of the active substance particles of the positive electrode material described in the present application is: the positive electrode material is dispersed in ethanol, and then the FC200s+HR particle morphology analyzer of OCCHIO is used as the test instrument (the camera resolution is 10 million pixels, the telecentric zoom lens, and the Callisto2012 version of the analysis and processing software), and the positive electrode material ethanol dispersion is pumped into the instrument sample pool through a 5mm sample tube. After image acquisition and analysis, the average Ai and A values ​​of the positive electrode material are confirmed, where Ai is the maximum inscribed circle area of ​​the positive electrode active substance particles, and A is the projected area of ​​the positive electrode active substance particles. Finally, the software automatically calculates the roundness of the positive electrode active substance particles in the positive electrode material through Rn=Ai / A.

[0026] In some embodiments, the roundness of the positive electrode active material particles can be adjusted by the calcination temperature and calcination time during the preparation process, but it is not limited to this. Those skilled in the art can also adjust it through common positive electrode active material particle preparation or processing methods such as ball milling process and spray treatment process according to actual needs.

[0027] In some embodiments, the 0.1%≤K≤0.5%.

[0028] More preferably, K is in the range of one or any two of 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%.

[0029] More preferably, the 0.2%≤K≤0.3%.

[0030] After acid etching, the proportion of free transition metal elements in the positive electrode active material particles is related to the type of positive electrode active material and the coating effect of the coating layer. Therefore, the size of K also affects the ion / electron transmission capacity and structural stability of the positive electrode active material particles. When the K value range of the positive electrode active material particles is preferably within the above range, the obtained positive electrode material has better structural stability and conductivity.

[0031] It should be noted that the test method for the K value of the positive electrode active material particles described in the present application is: the positive electrode material is placed in a 40wt% sodium hydroxide solution for digestion treatment, and then ICP is used for testing. The ICP test conditions are: the element detection spectrum wavelength is selected, and according to the characteristics of the sample and the elements to be detected, the appropriate ICP instrument working conditions are set, including a gas flow rate of 0.5L / min and a power of 1150W; the content of transition elements is tested by ICP to confirm the total content M1 of transition metal elements in the positive electrode active material particles (taking the positive electrode active material as lithium nickel manganese oxide as an example, the total content of transition metal elements is the total content of nickel and manganese. If lithium iron phosphate is taken as an example, it is iron The total content of the elements, if lithium nickel cobalt manganese oxide is taken as an example, it is the total content of nickel, cobalt and manganese); then, parallel samples are taken and immersed in a 20wt% hydrofluoric acid solution at a solid-liquid ratio of 1g:5mL at 70°C for 72 hours, and the supernatant of the hydrofluoric acid solution is taken for ICP testing. The ICP testing conditions are as follows: the element detection spectrum wavelength is selected, and according to the characteristics of the sample and the elements to be detected, appropriate ICP instrument working conditions are set, including a gas flow rate of 0.5L / min and a power of 1150W; the content of transition elements is tested by ICP to confirm the total content M2 of free transition metal elements after acid etching, and the final result is calculated according to K=M2 / M1*100%.

[0032] In some embodiments, the K can be regulated by the number of deposition turns of the coating layer during ALD atomic layer deposition, but is not limited to this. Those skilled in the art can also adjust other conditions during deposition, as well as other process conditions such as temperature and time during preparation and sintering of the positive electrode active material particles according to actual needs.

[0033] In some embodiments, the metal oxide includes at least one of aluminum oxide, tungsten oxide, and zirconium oxide.

[0034] The above-mentioned metal oxides as coating layers of the positive electrode active material particles can protect them from being corroded by acidic substances in the electrolyte, such as hydrofluoric acid, when in contact with the electrolyte, thereby producing by-products, affecting their electrochemical activity and service life; however, the metal oxides are not limited to the above-mentioned three types, and other metal oxides with similar inert protective effects can be used instead of the above-mentioned three types.

[0035] In some embodiments, the average particle size Dv50 of the positive electrode active material particles is 4 to 8 μm;

[0036] In the present application, the average particle size of the positive electrode active material particles is directly measured using a laser particle size analyzer.

[0037] In some embodiments, the concentration of the metal oxide in the positive electrode material is 100 to 4000 ppm.

[0038] In some embodiments, the positive electrode active material particles include at least one of lithium nickel cobalt manganese oxide particles, lithium iron phosphate particles, and lithium nickel manganese oxide particles.

[0039] The positive electrode active material particles in the positive electrode material described in the present application can be high-voltage positive electrode material lithium nickel manganese oxide particles, or can be layered structured ternary nickel cobalt lithium manganese oxide particles, whose chemical formula is LiNi x Co y Mn (1-x-y) O 2 , where 0<x<1, 0<y<1, or olivine structure lithium iron phosphate particles, whose chemical formula is LiFe x Mn 1-x PO 4 , wherein 0<x<1; as long as the ratio of the relationship between the K value and the roundness in the material is effectively regulated within a specific range of 0.2≤K / Rn≤1.2 after the surface coating layer is set, the structural stability can be improved compared with the conventional positive electrode materials of the same system, while the electrical conductivity is maintained at a high level, so that the material has ideal cycle performance and capacity performance when applied to secondary batteries, especially in high temperature environments.

[0040] In some embodiments, the positive electrode active material particles further include at least one of doped nickel cobalt lithium manganese oxide particles, doped lithium iron phosphate particles, and doped nickel lithium manganese oxide particles.

[0041] For the above three active material materials that are doped and modified, the modification methods in the present application and the positive electrode materials obtained after regulation can also achieve ideal electrochemical performance improvement. Therefore, the positive electrode active material particles described in the present application are not limited to the three undoped positive electrode materials.

[0042] In some embodiments, the positive electrode active material particles include lithium nickel manganese oxide particles, and 0.3≤K / Rn≤0.5.

[0043] In some embodiments, the positive electrode active material particles are LiNi x Mn y O 4 , where 0<x≤0.5, y=2-x.

[0044] Compared with ternary materials or lithium iron phosphate materials, lithium nickel manganese oxide particles have a higher operating voltage, so their stability is relatively poorer. Their structure has more edges and corners and low surface flatness. Therefore, it is necessary to specially control the coating effect of the coating layer to avoid the edges and corners on the surface from breaking when the pole piece is rolled, causing the coating layer on the surface to fail partially, and the probability of side reactions with the electrolyte is increased. When K / Rn is controlled within the range of 0.3 to 0.5, the positive electrode active material particles have a good coating effect, the edges and corners are fully coated and the surface flatness is high, the dissolution rate of transition metal elements is lower, and the conductive effect is higher, and the comprehensive use effect is better.

[0045] In an embodiment, the present application also provides a positive electrode plate, comprising the positive electrode material described in the present application.

[0046] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode material layer, and the positive electrode material layer includes the positive electrode material described in the present application.

[0047] In some embodiments, the positive electrode material layer further includes a conductive agent and a binder.

[0048] Further preferably, the conductive agent includes at least one of acetylene black and carbon nanotubes, and the binder includes polyvinylidene fluoride.

[0049] In an embodiment, the present application also provides a secondary battery, comprising the positive electrode plate described in the present application.

[0050] In some embodiments, the secondary battery further includes a negative electrode plate and an electrolyte.

[0051] In some embodiments, the negative electrode sheet includes a negative electrode active material.

[0052] In some embodiments, the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, and a silicon-carbon composite material.

[0053] Further preferably, the negative electrode material layer comprises a negative electrode material, a binder, a thickener and a conductive agent.

[0054] In some embodiments, the electrolyte includes a solvent and a lithium salt.

[0055] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.

[0056] Exemplarily, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.

[0057] Further preferably, the solvent may also include but is not limited to at least one of fluorinated derivatives of carbonate solvents, fluorinated derivatives of carboxylate solvents, fluorinated derivatives of ether solvents, fluorinated derivatives of sulfone solvents, fluorinated derivatives of nitrile solvents, and fluorinated derivatives of phosphate solvents.

[0058] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, and the like.

[0059] Further preferably, the concentration of the lithium salt in the electrolyte is 0.8 to 2.5 mol / L.

[0060] Further preferably, the concentration of the lithium salt in the electrolyte is in the range of one or any two of 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, and 2.5 mol / L.

[0061] In some embodiments, the secondary battery is prepared by the following method:

[0062] Preparation of positive electrode active material:

[0063] The lithium source, nickel source and manganese source are mixed at a target molar ratio, and mixed with zirconia balls with a diameter of 0.6-1.0 mm at a ball-to-material ratio of 5:1-8:1, and ball-milled at a rotation speed of 1700-2300 rpm for 5-12 hours. The ball-milled mixture is then calcined at a temperature of 600-1200°C for 6-20 hours and then cooled to room temperature to obtain spinel lithium nickel manganese oxide.

[0064] The lithium source options include: lithium carbonate, lithium hydroxide;

[0065] Nickel source selection: nickel hydroxide, nickel carbonate, nickel oxide;

[0066] Manganese source selection: manganese hydroxide, manganese carbonate, manganese oxide;

[0067] or:

[0068] The lithium source, nickel source, cobalt source and manganese source are mixed at a target molar ratio, and mixed with zirconium oxide balls with a diameter of 0.6-1.0 mm at a ball-to-material ratio of 5:1-8:1, and ball-milled at a rotation speed of 1700-2300 rpm for 5-12 hours. The ball-milled mixture is then calcined at a temperature of 600-1200° C. for 6-20 hours and then cooled to room temperature to obtain lithium nickel cobalt manganese oxide.

[0069] The lithium source options include: lithium carbonate, lithium hydroxide;

[0070] Nickel source selection: nickel hydroxide, nickel carbonate, nickel oxide;

[0071] Cobalt source selection: cobalt hydroxide, cobalt carbonate, cobalt oxide;

[0072] Manganese source selection: manganese hydroxide, manganese carbonate, manganese oxide;

[0073] or:

[0074] The lithium source, iron source and phosphorus source are mixed in a target molar ratio, and mixed with zirconium oxide balls with a diameter of 0.6-1.0 mm at a ball-to-material ratio of 5:1-8:1, and ball-milled at a rotation speed of 1700-2300 rpm for 5-12 hours. The ball-milled mixture is then calcined at a temperature of 500-800°C for 6-20 hours and then cooled to room temperature to obtain lithium iron phosphate.

[0075] The lithium source options include: lithium carbonate, lithium hydroxide;

[0076] Iron source selection: ferrous oxalate, ferrous acetate;

[0077] Phosphorus source selection: ammonium phosphate, diammonium phosphate;

[0078] The positive electrode active material, the conductive agent and the adhesive are dispersed in N-methylpyrrolidone (NMP) in a mass ratio of (94.0-99.85):(0.05-1.0):(0.1-5.0) to obtain a positive electrode slurry, and the positive electrode slurry is coated on an aluminum foil to obtain an aluminum foil with the positive electrode slurry coated on the surface; after drying, the aluminum foil is rolled and cut to obtain a positive electrode sheet.

[0079] The binder is selected from polytetrafluoroethylene or polyvinylidene fluoride.

[0080] The conductive agent is selected from one or more of conductive carbon black, acetylene black and carbon nanotubes.

[0081] The preparation method of the negative electrode sheet of the secondary battery is as follows:

[0082] The negative electrode material, the binder and the conductive agent are dispersed in deionized water according to a mass ratio of (93.0-99.8):(0.1-2.0):(0.1-5.0) to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil; after drying, cold pressing and cutting, the negative electrode sheet is obtained.

[0083] The negative electrode main material is selected from one or more of natural graphite, artificial graphite, soft carbon and hard carbon;

[0084] The binder is selected from one or more of polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC);

[0085] The conductive agent is selected from conductive carbon black and / or carbon nanotubes.

[0086] The preparation method of the electrolyte of the secondary battery is:

[0087] The solvent and the lithium salt are mixed in a mass ratio of (98-99.99):(0.01:2) to obtain an electrolyte.

[0088] The solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate solvents.

[0089] The carbonate solvent is selected from at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent is selected from at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent is selected from at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent is selected from at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent is selected from at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent is selected from at least one of trimethyl triphosphate and triethyl phosphate.

[0090] Lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2), at least one of lithium difluorobis(oxalate) phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0091] After obtaining the components, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound in sequence to assemble into a battery cell, packaged, injected with electrolyte, packaged, formed and fixed in capacity to obtain the secondary battery.

[0092] Among them, the electrolyte of the secondary battery described in the present application is compounded with various suitable types of solvents and lithium salts according to actual needs, and the concentration of the lithium salt is adjusted at the same time. As long as the normal use effect can be achieved, it is not limited by the described scheme.

[0093] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0094] Example 1

[0095] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0096] (1) Preparation of positive electrode materials: Li 2 CO 3 、NiCO 3 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C in an air atmosphere for H h, and then heated to 850 °C for 12 h to obtain the positive electrode active material particles LiNi 0.5 Mn 1.5 O 4 Then, an ALD atomic deposition instrument is used to deposit aluminum oxide powder as a raw material, a deposition pressure h is set, and the number of deposition cycles is set to C cycles, and aluminum oxide is deposited on the surface of the positive electrode active material particles to obtain a positive electrode material;

[0097] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0098] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0099] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0100] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0101] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0102] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0103] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0104] Embodiments 2 to 14

[0105] A positive electrode material and a secondary battery, which are different from those in Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0106] Embodiments 15 to 18

[0107] A positive electrode material and a secondary battery, which are different from Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, and the raw material for ALD deposition is replaced by zirconium oxide powder, as shown in Table 1.

[0108] Examples 19 to 22

[0109] A positive electrode material and a secondary battery, which are different from those in Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, and the raw material for ALD deposition is replaced with tungsten oxide powder, as shown in Table 1.

[0110] Embodiments 23 to 28

[0111] A positive electrode material and a secondary battery, which are different from those in Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0112] Embodiment 29

[0113] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0114] (1) Preparation of positive electrode materials: Li 2 CO 3 、NiCO 3 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C in an air atmosphere for H h, and then heated to 850 °C for 12 h to obtain the positive electrode active material particles LiNi 0.5 Mn 1.5 O 4 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.2 Mn 1.8 O 4 ;

[0115] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0116] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0117] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0118] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0119] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0120] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0121] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0122] Embodiment 30

[0123] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0124] (1) Preparation of positive electrode materials: Li 2 CO 3 、NiCO 3 、Co(OH) 2 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T℃ in an air atmosphere for H h, and then heated to 900℃ for 12 h to obtain the positive electrode active material particles LiNi 0.4 Co 0.2 Mn 0.4 O 2 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.4 Co 0.2 Mn 0.4 O 2 ;

[0125] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0126] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0127] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0128] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0129] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0130] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0131] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0132] Embodiment 31

[0133] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0134] (1) Preparation of positive electrode materials: Li 2 CO 3 、FeC 2 O 4 ·2H 2 O and NH 4 H 2 PO 4 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C for H h in an argon atmosphere, and then heated to 750 °C for 12 h to obtain the positive electrode active material particles LiFePO 4 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiFePO 4 ;

[0135] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0136] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0137] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0138] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0139] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0140] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0141] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0142] Comparative Examples 1 to 4

[0143] A positive electrode material and a secondary battery, which are different from those in Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0144] Comparative Examples 5-6

[0145] A positive electrode material and a secondary battery, which are different from Example 1 only in that the preparation process parameters of the positive electrode material and the characteristic parameters of the obtained positive electrode material are different, and the raw material for ALD deposition is replaced by zirconium oxide powder, as shown in Table 1.

[0146] Comparative Example 7

[0147] A positive electrode material and a secondary battery, (1) Preparation of the positive electrode material: Li 2 CO 3 、NiCO 3 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C in an air atmosphere for H h, and then heated to 850 °C for 12 h to obtain the positive electrode active material particles LiNi 0.5 Mn 1.5 O 4 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.2 Mn 1.8 O 4 ;

[0148] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0149] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0150] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0151] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0152] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0153] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0154] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0155] Comparative Example 8

[0156] A positive electrode material and a secondary battery, (1) Preparation of the positive electrode material: Li 2 CO 3 、NiCO 3 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C in an air atmosphere for H h, and then heated to 850 °C for 12 h to obtain the positive electrode active material particles LiNi 0.5 Mn 1.5 O 4 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.2 Mn 1.8 O 4 ;

[0157] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0158] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0159] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0160] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0161] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0162] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0163] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0164] Comparative Example 9

[0165] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0166] (1) Preparation of positive electrode materials: Li 2 CO 3 、NiCO 3 、Co(OH) 2 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T℃ in an air atmosphere for H h, and then heated to 900℃ for 12 h to obtain the positive electrode active material particles LiNi 0.4 Co 0.2 Mn 0.4 O 2 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.4 Co 0.2 Mn 0.4 O 2 ;

[0167] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0168] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0169] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0170] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0171] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0172] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0173] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0174] Comparative Example 10

[0175] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0176] (1) Preparation of positive electrode materials: Li 2 CO 3 、NiCO 3 、Co(OH) 2 and MnO 2 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T℃ in an air atmosphere for H h, and then heated to 900℃ for 12 h to obtain the positive electrode active material particles LiNi 0.4 Co 0.2 Mn 0.4 O 2 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiNi 0.4 Co 0.2 Mn 0.4O 2 ;

[0177] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0178] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0179] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0180] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0181] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0182] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0183] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0184] Comparative Example 11

[0185] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0186] (1) Preparation of positive electrode materials: Li 2 CO 3 、FeC 2 O 4 ·2H 2 O and NH 4 H 2 PO 4 According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C for H h in an argon atmosphere, and then heated to 750 °C for 12 h to obtain the positive electrode active material particles LiFePO 4Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiFePO 4 ;

[0187] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0188] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0189] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0190] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0191] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0192] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0193] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0194] Comparative Example 12

[0195] A positive electrode material and a secondary battery, wherein the preparation method comprises the following steps:

[0196] (1) Preparation of positive electrode materials: Li 2 CO 3 、FeC 2 O 4 ·2H 2 O and NH 4 H 2 PO 4According to the stoichiometric ratio, Bh was ball-milled at a rate of A, and then sintered at T °C for H h in an argon atmosphere, and then heated to 750 °C for 12 h to obtain the positive electrode active material particles LiFePO 4 Then, an ALD atomic deposition instrument was used to deposit aluminum oxide powder as raw material, the deposition pressure was set to h, and the number of deposition cycles was set to C cycles. Aluminum oxide was deposited on the surface of the positive electrode active material particles to obtain the positive electrode material LiFePO 4 ;

[0197] The preparation and characteristic parameters of the positive electrode material are shown in Table 1;

[0198] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and dried, cold pressed and cut to obtain the positive electrode sheet;

[0199] The resistance value of the obtained positive electrode sheet is directly tested by using a resistance meter;

[0200] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring. The slurry is then coated on both sides of the current collector copper foil, dried, cold pressed, and cut to obtain the negative electrode sheet. The negative electrode material is graphite.

[0201] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0202] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate were mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF was added. 6 Dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L;

[0203] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0204] Table 1

[0205]

[0206]

[0207] Effect example

[0208] The positive electrode materials and secondary batteries obtained in each embodiment and comparative example were tested as follows:

[0209] (1) Positive electrode sheet resistance test: directly test as described above, no further details will be given;

[0210] (2) High temperature cycle performance test: The secondary batteries obtained in each embodiment and comparative example were preliminarily charged at room temperature to the upper voltage limit using the LAND charge and discharge system at a constant current of 0.33C; then discharged at a constant current to the lower voltage limit at a rate of 0.33C for 2 cycles, and then placed in a 45°C environment and charged and discharged at the same system at the same working voltage for 100 times at a rate of 1C / 1C, and the discharge capacity at each cycle number was counted, and finally the high temperature cycle capacity retention rate (%) was counted = discharge capacity of the secondary battery after 100 cycles at a rate of 1C / 1C / discharge capacity of the secondary battery in the first cycle at a rate of 1C / 1C;

[0211] The voltage lower limit of the secondary batteries obtained in Examples 1 to 29 and Comparative Examples 1 to 8 is 2.5 V, and the voltage upper limit is 4.25 V;

[0212] The corresponding lower voltage limit of the secondary batteries obtained in Example 30 and Comparative Examples 9 to 10 is 3.7V, and the upper voltage limit is 4.2V;

[0213] The corresponding lower voltage limit of the secondary batteries obtained in Example 31 and Comparative Examples 11 to 12 is 2.2V, and the upper voltage limit is 3.7V;

[0214] (3) High temperature storage performance test: The secondary batteries obtained in each embodiment and comparative example were preliminarily charged at room temperature to the upper voltage limit using the LAND charge and discharge system at a rate of 0.33C; then discharged at a constant current to the lower voltage limit at a rate of 0.33C, and cycled twice, and then placed in a 45°C environment for storage for 15 days. After the storage was completed, the batteries were taken out and cycled once at the same rate at the same operating voltage using the same system at room temperature. The high temperature storage capacity retention rate (%) was finally calculated as follows: discharge capacity of the secondary battery after cycling at a rate of 0.33C at room temperature after storage / discharge capacity of the secondary battery after cycling at a rate of 0.33C at room temperature after storage;

[0215] The voltage lower limit of the secondary batteries obtained in Examples 1 to 29 and Comparative Examples 1 to 8 is 2.5 V, and the voltage upper limit is 4.25 V;

[0216] The corresponding lower voltage limit of the secondary batteries obtained in Example 30 and Comparative Examples 9 to 10 is 3.7V, and the upper voltage limit is 4.2V;

[0217] The corresponding lower voltage limit of the secondary batteries obtained in Example 31 and Comparative Examples 11 to 12 is 2.2V, and the upper voltage limit is 3.7V;

[0218] The test results are shown in Table 3.

[0219] Table 2

[0220]

[0221]

[0222]

[0223] From Table 2 we can see that:

[0224] (1) The positive electrode material described in the present application is provided with a coating layer on the surface of the positive electrode active material, and the roundness of the coated positive electrode material and the ratio of the content of free transition metal ions after acid corrosion are regulated to coordinate the balance between stability and conductivity in the positive electrode material, so that the secondary battery prepared by the positive electrode material has ideal electrochemical performance. It can be seen that the resistance value of the positive electrode sheet obtained in each embodiment is relatively low, with a maximum of only 300mΩ. The secondary battery further prepared by the positive electrode sheet can achieve a cycle capacity retention rate of at least 80% in a high temperature environment, and after 15 days of high temperature storage, the capacity retention rate of the battery can reach at least 79%, with excellent comprehensive performance. In contrast, although the positive electrode materials obtained in Comparative Examples 1 to 10 also have a coating layer, the balance between roundness and stability of transition metal elements is not regulated. Not only can the resistance value of the positive electrode material not be guaranteed to be at a low level after being prepared into a positive electrode sheet, but the high temperature performance is also poor, and the ideal high temperature stability cannot be exerted after being prepared into a secondary battery.

[0225] (2) According to Examples 1 to 15 and Examples 16 to 29, it can be seen that when the positive electrode material in the present application is set, the types of the positive electrode active material and the coating layer are not limited. Especially when the positive electrode active material is lithium nickel manganese oxide, when K / Rn is controlled within the range of 0.3 to 0.5, the positive electrode active material particles have a good coating effect, the edges and corners are fully coated and the surface flatness is high, the dissolution rate of transition metal elements is lower, and the conductive effect is higher. The comprehensive use effect is better, the resistance value of the positive electrode sheet prepared by the positive electrode material can be maintained within 270mΩ, and the capacity retention rate after high-temperature cycling and high-temperature storage can reach more than 85%.

[0226] (3) When regulating the positive electrode material, the roundness of the positive electrode active material particles after setting the coating layer will affect the coating integrity and regularity of the overall particles, which will lead to different contact areas between the material particles and the electrolyte, and different compaction tightness and structural stability when used to prepare the electrode. When the roundness of the material is preferably in the range of 0.6 to 0.7, the positive electrode active material particles can achieve a moderate contact area when in contact with the electrolyte, and the balance between the probability of transition metal ion dissolution and the difficulty of ion / electron transmission of the material can be regulated by the degree of coating, and the ideal electrode stability and density can be achieved when preparing the positive electrode; on the other hand, after acid etching, the content of free transition metal elements in the positive electrode active material particles accounts for 2.3% of the total free transition metal element content. The size is related to the type of positive electrode active material and the coating effect of the coating layer. Therefore, the size of K also affects the ion / electron transmission capacity and structural stability of the positive electrode active material particles. When the K value range of the positive electrode active material particles is preferably between 0.2 and 0.3%, the obtained positive electrode material has better structural stability and conductivity. When the obtained positive electrode material satisfies both preferences at the same time and the constructed proportional relationship is also within the preferred range, the positive electrode sheet prepared from the obtained positive electrode material can not only maintain a resistance value within 230mΩ, but also when used to prepare secondary batteries, the capacity retention rate after high-temperature cycling and high-temperature storage can reach more than 90%, the high-temperature cycling capacity retention rate can reach up to 95%, and the capacity retention rate after high-temperature storage can reach 94%.

Claims

1. A positive electrode material, characterized in that: The invention comprises positive electrode active material particles, wherein the positive electrode active material particles are provided with a coating layer, and the coating layer comprises a metal oxide; The positive electrode material satisfies: 0.2≤K / Rn≤1.2; The K% is the content ratio of the free transition metal element in the positive electrode active material particles after the positive electrode active material particles are immersed in a 20 wt % hydrofluoric acid solution at a solid-liquid ratio of 1 g:5 mL at 70° C. for 72 hours. The Rn is the roundness of the positive electrode active material particles.

2. The positive electrode material according to claim 1, characterized in that The 0.4≤Rn≤0.

8.

3. The positive electrode material according to claim 2, characterized in that The 0.6≤Rn≤0.

7.

4. The positive electrode material according to claim 1, characterized in that The 0.1%≤K≤0.5%.

5. The positive electrode material according to claim 4, characterized in that The 0.2%≤K≤0.3%.

6. The positive electrode material according to claim 1, characterized in that The positive electrode active material particles include at least one of lithium nickel cobalt manganese oxide particles, lithium iron phosphate particles, and lithium nickel manganese oxide particles.

7. The positive electrode material according to claim 6, characterized in that The positive electrode active material particles include lithium nickel manganese oxide particles, and the 0.3≤K / Rn≤0.

5.

8. The positive electrode material according to claim 1, characterized in that The metal oxide in the coating layer includes at least one of aluminum oxide, tungsten oxide and zirconium oxide.

9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: It comprises the secondary battery as claimed in claim 9, and the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Lithium manganese positive electrode active material having spinel structure, and positive electrode and lithium secondary battery comprising same

    CN110574194A

  • Positive plate, and electrochemical device and electronic device comprising same

    CN113795953A

  • Preparation method of positive electrode active material for secondary battery

    CN114762148A

  • Recycling method of positive electrode material, positive electrode plate and secondary battery

    CN115842185A

  • Secondary battery and electric device

    CN115881892A

Cited By

  • Secondary battery and electric device

    CN120565778A

  • Secondary batteries and electrical appliances

    CN120565778B